New Pharmacologic Approaches in Hypertension: Baxdrostat and Zilebesiran with Insights from BaxHTN and KARDIA-3 Trials - Skibicka, Katarzyna; Skibicki, Tomasz; Wesołowsla, Weronika; Pietrzak, Jarosław (Journal of Education, Health and Sport, 2025)
Background: Resistant and uncontrolled hypertension remains a major cardiovascular risk factor worldwide. Emerging therapies targeting the renin-angiotensin-aldosterone system (RAAS), including Baxdrostat and Zilebesiran, offer potential benefits. Objective: To systematically evaluate the pharmacologic rationale, clinical efficacy, and safety of Baxdrostat and Zilebesiran in patients with uncontrolled or resistant hypertension. Methods: A systematic literature search was conducted in PubMed, Embase, and Cochrane Library (2018–2025) using terms “Baxdrostat,” “Zilebesiran,” “resistant hypertension,” “aldosterone synthase inhibitor,” “RNA interference,” and related MeSH terms. Studies in English reporting clinical trial outcomes for Baxdrostat or Zilebesiran were included. Reviews, commentaries, and animal studies were excluded. Two independent reviewers screened titles, abstracts, and full texts; conflicts were resolved by consensus. Twenty-four publications were included, comprising phase II/III trials, mechanistic studies, and meta-analyses. Results: Baxdrostat and Zilebesiran significantly reduce systolic and diastolic blood pressure in resistant hypertension. Baxdrostat selectively inhibits aldosterone synthase, whereas Zilebesiran silences hepatic angiotensinogen via siRNA. Both agents show favorable safety profiles, with minimal adverse effects. Conclusion: These emerging RAAS-targeting therapies provide mechanism-based options for patients with resistant or uncontrolled hypertension, highlighting the potential for phenotype-guided, precision therapy. Further long-term studies are needed to evaluate cardiovascular outcomes and comparative effectiveness.